Factorization of a convolution-type integro-differential equation on the positive half line - Khachatryan, A. Kh.; Khachatryan, Kh. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Sufficient conditions for the existence of solutions are obtained for a class of convolution-type integro-differential equations on the half line. The investigation is based on the three-factor decomposition of the initial integro-differential operator.